2004
DOI: 10.1080/1612197x.2004.9671737
|View full text |Cite
|
Sign up to set email alerts
|

Mood and concentration grid performance: Effects of depressed mood

Abstract: The current study tested Lane and Terry's (2000) proposal that depressed mood moderates anger?performance and tension?performance relationships. One hundred and thirty?six male sport students completed the 24?item Brunel Mood Scale followed by a concentration grid test. Participants were dichotomized into depressed mood (n = 59) and no depression (n = 77) groups. Structural equation modeling showed that mood predicted 41% of performance variance in the no?depression group and 31% in the depressed?mood group. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…Dalam situasi pertandingan, seorang atlet akan berhadapan dengan hal-hal yang akan mengganggu konsentrasinya, mulai dari aspek mental psikologis yang dapat membuat atlet tersebut menurun tingkat konsentrasinya yang akan mengakibatkan turunnya performa (Lane et al, 2004;McCarthy et al, 2013;Swann et al, 2017), faktor anxiety atau kepanikan juga dapat mempengaruhi konsentrasi yang akhirnya berpengaruh terhadap performa (Behan & Wilson, 2008;Prior & Coates, 2019 Medeiros Filho et al, 2008), melainkan kemampuan konsentrasinya juga harus dilatih. Terlebih apabila atlet tersebut akan bertanding pada jarak target yang lebih jauh (Behan & Wilson, 2008) Semakin tinggi tingkat konsentrasi seorang atlet panahan, maka hasil yang akan diperolehnya pun akan semakin baik dan konsisten.…”
Section: Pendahuluanunclassified
“…Dalam situasi pertandingan, seorang atlet akan berhadapan dengan hal-hal yang akan mengganggu konsentrasinya, mulai dari aspek mental psikologis yang dapat membuat atlet tersebut menurun tingkat konsentrasinya yang akan mengakibatkan turunnya performa (Lane et al, 2004;McCarthy et al, 2013;Swann et al, 2017), faktor anxiety atau kepanikan juga dapat mempengaruhi konsentrasi yang akhirnya berpengaruh terhadap performa (Behan & Wilson, 2008;Prior & Coates, 2019 Medeiros Filho et al, 2008), melainkan kemampuan konsentrasinya juga harus dilatih. Terlebih apabila atlet tersebut akan bertanding pada jarak target yang lebih jauh (Behan & Wilson, 2008) Semakin tinggi tingkat konsentrasi seorang atlet panahan, maka hasil yang akan diperolehnya pun akan semakin baik dan konsisten.…”
Section: Pendahuluanunclassified
“…J. Sport Tourism 2016, 23,[21][22][23][24] less effective athletes who experienced a higher level of friendliness and lower level of anger.…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that there was a negative correlation between the pentathletes' level of friendliness and their performance outcome. It is worth noting that although analyses conducted by other authors have shown that athletes who have better outcomes may experience a higher level of anger [22,23], it has been stated that this is only possible when other negative POMS variables are low [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent tests of Lane and Terry's (2000) model have found supportive evidence in a range of different areas of application including sport (see Lane, 2007;, exercise (Lane & Lovejoy,2001), concentration tasks (Lane, Terry, Beedie, & Stevens, 2004), endurance performance (Lane, 2001) and academic performance (Lane, Whyte, Terry, & Nevill, 2005). One of its strengths is that studies have investigated emotional states in naturally-occurring phenomena and therefore, fi ndings have ecological validity.…”
Section: Profi Le Of Mood States and Performancementioning
confidence: 99%